Konversi Pelepah Nipah Menjadi Bio - Oil Dengan Variasi Katalis NiMo/Lempung Cengar Memalui Proses Pirolisis - Surya Romadani; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bio-oil is one of the alternative energy that can be used as a substitute for petroleum. Riau has huge potential in Nipah and clay which not be used widely. Bio-oil can be produced through pyrolysis process  of Nipah  with catalyst  NiMo/ Cengar Clay. Theaimings of this study is to determine the effect of variations in catalyst NiMo/ Cengar Clay and characterize the physical and chemical properties of the yield of bio-oil produced. In this study the pyrolysis  process carried out at 320 °C of temperature,300 rpm  stirrer speed, 500 ml  of silinap and50 grams of biomass  in +100-200 mesh size.Variation of the catalysts are0, 0.5, 1.5 and 2.5 % w/w. The results of this study indicated that the optimum yield was obtained in 0.5 % catalyst NiMo/ Cengar Clay, which is 63.64 %. The analysist  results of the physical properties of bio-oil are density of 0.884 g/ ml, 9.486 cSt of viscosity, 47.92 gr NaOH/100 gr sample of acid number, 45.47 MJ/Kg of the calor value, and 54°C of flash point. The results of chemical analysis by GC - MS , obtained some chemical components such as Acetic acid, Butyric Acid, 2,2-Dimethoxy-Ethanol, Furfural , 4-Hydroxy-Butyric Acid, Phenol, O-Cresol , 2-Methoxy-6-methyl-phenol and catechol. The  characteristic  results  have been  obtained  is approaching the characteristics of fuel oil and bio-oil standard. Keywords : Bio-oil, pyrolysis, Nipah and NiMo Catalyst/ Cengar Clay